RESPON PERTUMBUHAN DAN HASIL DUA VARIETAS TANAMAN KAILAN (Brassica oleraceae L.) AKIBAT SUBSTITUSI PUPUK N-ANORGANIK DENGAN PUPUK HIJAU LAMTORO - Nila Apriliani; Sumarsono Sumarsono; Sutarno Sutarno (Percetakan Umi Toaha Makassar, 2021)
The use of organic fertilizers required to improve of soil quality. The study examine the substitution of nitrogen inorganic fertilizers with green manure on the different varieties of nova and winsa on the growth and yield. The study used a factorial experiment 5 x 2 of randomized completely design with four replications. The first factor was substitutions nitrogen inorganic fertilization with Leucaena leucocephala green manure in the various of S0 = 100% nitrogen inorganic fertilization (control), S1 = 75% urea fertilizer + 25% green manure, S2 = 50% urea fertilizer + 50% green manure, S3 = 25% urea fertilizer + 75% green manure, S4 = 100% green manure. The second factor the different varieties of hook. In the various of V1 = nova, V2 = winsa. The data of result study obtained were analyzed by analysis of variance (ANOVA), then proced by the Duncan test to find out the different of each treatmet. The result showed that a real interaction treatment of substitution inorganic fertilization with green manure on the two varieties is number of leaves, wet weight of shoot, dry weight of shoot, ratio of shoot and root, where there is not real interaction with treatment of plant height and chlorophyll content. On the nova varieties dosing 50% inorganic fertilization + 50% green manure can produce wet weight of shoot, dry weight of shoot, ratio of shoot and root highest.